2022
DOI: 10.3389/fcimb.2022.821429
|View full text |Cite
|
Sign up to set email alerts
|

New Advances in Improving Bone Health Based on Specific Gut Microbiota

Abstract: The gut microbiota has been shown to play an important role in the pathogenesis of various diseases, including metabolic diseases, cardiovascular diseases, and cancer. Recent studies suggest that the gut microbiota is also closely associated with bone metabolism. However, given the high diversity of the gut microbiota, the effects of different taxa and compositions on bone are poorly understood. Previous studies demonstrated that the mechanisms underlying the effects of the gut microbiota on bone mainly includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…This F/B ratio was negatively correlated with bone volume. 37 In this study, the administration of Lp. plantarum GMNL-662 was shown to enhance the number of several probiotic species, including Lp.…”
Section: Food and Function Papermentioning
confidence: 96%
“…This F/B ratio was negatively correlated with bone volume. 37 In this study, the administration of Lp. plantarum GMNL-662 was shown to enhance the number of several probiotic species, including Lp.…”
Section: Food and Function Papermentioning
confidence: 96%
“…Switching to a very low carbohydrate KD from a higher carbohydrate diet changes the intestinal microbiome [48], which may influence bone outcomes [49]. Potential mechanisms through which the microbiome might impact bone include changes in signaling by microbial metabolites, mucin production and gut integrity, and the absorption of nutrients including calcium [50,51].…”
Section: Altered Intestinal Microbiomementioning
confidence: 99%
“…Cinnamic acid suppresses bone loss via induction of osteoblast differentiation with the alteration of gut microbiota ( Hong et al, 2022 ). Studies have also found that external interventions such as dietary changes can alter the gut microbiota composition and improve bone health ( Yan et al, 2022 ). Overall, multiple factors, including hereditary, dietary and physical factors could alter the gut microbiota composition and further regulate bone metabolism ( Yan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%